STATE AND TRAIT ANXIETY, VEGETATIVE STATUS AND FUNCTIONAL CAPABILITIES OF ADOLESCENTS WITH GASTRO-OESOPHAGEAL REFLUX DISEASE - Beketova, Halyna; Moshchych Оstap; Malinovska, Daria; Beketova, Nataliia; Moshchych, Oleksandr (Eastern Ukrainian Medical Journal, 2025)
The article presents our own research data related to the study of psycho-vegetative characteristics and functional capabilities of adolescents with gastroesophageal reflux disease (GERD), including obese patients. The aim of the study was to determine the levels of state and trait anxiety, vegetative status and functional capabilities in adolescents of GERD to justify the need for differentiated psycho-vegetative correction in the complex treatment of the disease. Materials and methods of research. 35 healthy adolescents (control group I) and 81 children aged 15–17 years with GERD (main group II) were examined, including 47 patients with its non-erosive form (subgroup IIn) and 34 with erosive reflux-esophagitis (subgroup IIe), including 9 girls with overweight (OW) and obesity. The levels of trait (TA) and state anxiety (SA) were determined using the State-Trait Anxiety Inventory; vegetative status and functional capabilities – using the author's computer program (Ukrainian utility model Patent No. 143026 dated 10.07.20). Statistical processing of the obtained results was carried out using generally accepted methods of medical statistics. Research results. 61.7 % of adolescents with non-erosive GERD and 64.7 % with erosive reflux-esophagitis showed sympathicotonia and unsatisfactory functional capabilities (83.0 % and 97.0 %) in the absence of gender differences and regardless of the presence of OW and obesity. In Group II, there was mainly an average level of TA (63.8 %) and SA (53.2 %) without significant gender differences. In erosive esophagitis, the majority of patients showed a high level of both TA (70.6 %) and SA (55.9 %) with a predominance of girls (81.3 % and 75.0 % against 61.1 % and 38.9 % in boys). The most pronounced psychological disorders were found in adolescent girls with erosive esophagitis and OW and obesity – high levels of TA (100.0 %) and CA (88.9 %) against the background of sympathicotonia and unsatisfactory functional capabilities. Conclusion. Most adolescents with GERD, and especially girls with OW and obesity, have psychological and vegetative disorders and unsatisfactory functional capabilities, which can be both a background for the formation of the disease and its consequence, and require early detection and timely therapy with psychological support to improve the quality of life and prevent the formation of severe complications.